2019
DOI: 10.1029/2019sw002202
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectric Field Evaluation During the September 2017 Geomagnetic Storm: MA.I.GIC. Model

Abstract: The space environment near Earth is constantly subjected to changes in the solar wind flow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…No loss of lock has been found, contrary to what happened, for instance, during the well-known and much more intense (i.e. Dst -Disturbed Storm Time indexminimum value reached of −230 nT) St Patrick's Day storm that occurred on 17 March 2015 (Jin and Oksavik, 2018;De Michelis et al, 2016;Pignalberi et al, 2016), where vTEC measurements highlighted many losses of lock (figures not shown). The fact that no loss of lock has been found during the August geomagnetic storm means that the event was weak in terms of space weather effects on navigation systems.…”
Section: Ionospheric Responsementioning
confidence: 58%
“…No loss of lock has been found, contrary to what happened, for instance, during the well-known and much more intense (i.e. Dst -Disturbed Storm Time indexminimum value reached of −230 nT) St Patrick's Day storm that occurred on 17 March 2015 (Jin and Oksavik, 2018;De Michelis et al, 2016;Pignalberi et al, 2016), where vTEC measurements highlighted many losses of lock (figures not shown). The fact that no loss of lock has been found during the August geomagnetic storm means that the event was weak in terms of space weather effects on navigation systems.…”
Section: Ionospheric Responsementioning
confidence: 58%
“…A number of additional geospace effects with notable potential to produce significant impacts on technological systems were also observed at Earth during this period. For instance, rapid changes in the terrestrial magnetic field environment caused strong geomagnetically induced currents, a phenomenon that can damage critical technological infrastructures that contain ground‐based conducting systems, such as power grids, railways, telecommunication cables, and oil and gas pipelines (Clilverd et al., 2018; Dimmock et al., 2019; Piersanti et al., 2019). The SEPs, which were identified to enter the magnetosphere, likewise increased the likelihood of failures in spacecraft electronics (O'Brien et al., 2018), and on the International Space Station, the Moon, and Mars, increased radiation doses were observed (Berger et al., 2018; Hassler et al., 2018; Schwadron et al., 2018).…”
Section: Solar Storms Of September 2017 and Their Effects At Earth Anmentioning
confidence: 99%
“…While detailed study of the spaceweather events and their geomagnetic impacts during September 2017 are previously well reported (e.g. Attie et al, 2018;Berger et al, 2018;Chamberlin et al, 2018;Chertok, Belov, and Abunin, 2018;Matthiä, Meier, and Berger, 2018;O'Brien, Mazur, and Looper, 2018;Redmon et al, 2018;Schillings et al, 2018;Yan et al, 2018;Bruno et al, 2019;Jiggens et al, 2019;Piersanti et al, 2019;Werner et al, 2019;Zou et al, 2019;Scolini et al, 2020;Hajra, Tsurutani, and Lakhina, 2020, and the references therein), there is no quantitative study of the magnetic reconnection for this period. The latter is the main topic of the present work.…”
Section: Introductionmentioning
confidence: 99%